Demographic trends in community functional tolerance reflect tree responses to climate and altered fire regimes. Issue 8 (21st July 2020) - Marshall, L. A.; Falk, D. A.
Abstract: Forests of the western United States are undergoing substantial stress from fire exclusion and increasing effects of climate change, altering ecosystem functions and processes. Changes in broad‐scale drivers of forest community composition become apparent in their effect on survivorship and regeneration, driving demographic shifts. Here we take a community functional approach to forest demography, by investigating mean drought or shade functional tolerance in community assemblages. We created the Community Mean Tolerance Index (CMTI), a response metric utilizing drought/shade tolerance trade‐offs to identify communities undergoing demographic change from a functional trait perspective. We applied the CMTI to Forest Inventory and Analysis data to investigate demographic trends in drought and shade tolerance across the southern Rocky Mountains. To find the major drivers of change in community tolerance within and across forest types, we compared index trends to climate and fire‐exclusion‐driven disturbance, and identified areas where demographic change was most pronounced. We predicted that greater shifts in drought tolerance would occur at lower forest type ecotones where climate stress is limiting and that shifts in shade tolerance would correspond to excursions from the historic fire regime leading to greater changes in forest types adapted to frequent, low‐intensity fire. The CMTI was applied spatially to identify sites likely to transition to oak shrubfield, where disturbance history combined with a species‐driven demographic shift toward drought tolerance. Within forest types, lower elevations are trending toward increased drought tolerance, while higher elevations are trending toward increased shade tolerance. Across forest types, CMTI difference peaked in mid‐elevation ponderosa pine and mixed‐conifer forests, where fire exclusion and autecology drive demographic changes. Peak CMTI difference was associated with fire exclusion in forest types adapted to frequent fire. At higher elevations, site‐level stand dynamics appear to be influencing demographic tolerance trends more than broad climate drivers. Through a community demographic approach to functional traits, the CMTI highlights areas and forest types where ecosystem function is in the process of changing, before persistent vegetation type change occurs. Applied to regional plot networks, the CMTI provides an early warning of shifts in community functional processes as climate change pressures continue.